Possessive without Concordance in Galician and in Galician Spanish as a Syntactic Change in Progress - Silva-Domínguez, Carme (Madrygal. Revista de Estudios Gallegos, 2021)
This article offers an analysis of two forms of the so-called Possessive without agreement that are possible in Galician and in Galician Spanish. First of all, it deals with the well-known progress of the possessive paradigm to structures that are nucleated by an adverb of place, like diante miña. Secondly, the constructions like ao lado súa, where the (2) possessive pronoun appears without agreement and whose meaning can be locative, and others are also studied. The analysis consists of (3) accessing and using the TILG, CORGA and CORILGA corpus for Galician, and the ESLORA corpus for Galician Spanish. Aspects which are described are the chronology of the phenomenon and the relevance of factors such as the grammatical person, the kind of adverb or adverbial locution, the level of animation in the antecedent: all of them are analysed to explain their ability to promote innovation. Arguments supporting the interpretation of the remodelling as a change from below are provided, and two attempts to operate a change from above in the innovation are also described. Finally, the article offers evidence for the interpretation of the linguistic remodelling as endogenous; the peculiar phenomenon that consists of the selection of the feminine genre for the possessive form in both linguistic systems is studied as well.